2012
DOI: 10.1681/asn.2011030310
|View full text |Cite
|
Sign up to set email alerts
|

Mannose Receptor 2 Attenuates Renal Fibrosis

Abstract: Mannose receptor 2 (Mrc2) expresses an extracellular fibronectin type II domain that binds to and internalizes collagen, suggesting that it may play a role in modulating renal fibrosis. Here, we found that Mrc2 levels were very low in normal kidneys but subsets of interstitial myofibroblasts and macrophages upregulated Mrc2 after unilateral ureteral obstruction (UUO). Renal fibrosis and renal parenchymal damage were significantly worse in Mrc2-deficient mice. Similarly, Mrc2-deficient Col4a3 2/2 mice with here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
62
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 74 publications
0
62
0
Order By: Relevance
“…Nevertheless, MMP14, -1, and -13 all have well-described matrix-degrading functions at the cell surface, whereas MMP2 and -9 may play minor roles in extracellular degradation of fibrillar matrix (83,90,91). Evidence from models of fibrosis regression indicates reparative macrophages both enzymatically cleave and endocytose matrix, which is subsequently degraded by cathepsins in lysosomes (79,(92)(93)(94).…”
Section: Resolution Of Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, MMP14, -1, and -13 all have well-described matrix-degrading functions at the cell surface, whereas MMP2 and -9 may play minor roles in extracellular degradation of fibrillar matrix (83,90,91). Evidence from models of fibrosis regression indicates reparative macrophages both enzymatically cleave and endocytose matrix, which is subsequently degraded by cathepsins in lysosomes (79,(92)(93)(94).…”
Section: Resolution Of Fibrosismentioning
confidence: 99%
“…Mannose-C receptors (CD206 and Endo180) specifically endocytose collagen fragments in subsets of tissue macrophages (79,94) in kidney and skin disease, whereas discoidin-domainreceptor (DDR) family members bind fibrillar collagen but likely do not internalize it (95). Intriguingly, the plasma globulin MFGE8 has been reported to bind collagen via discoid domains and facilitate turnover by macrophages via an integrin-independent mechanism in lung disease (80).…”
Section: Resolution Of Fibrosismentioning
confidence: 99%
“…Whereas attempts have been made to modulate the activity of matrix-degrading enzymes, in particular of MMPs, as yet no useful therapies have emerged (21). Other approaches targeting ECM turnover might be successful as example shown for mannose receptor 2 (344). Another attractive therapeutic approach for fibrosis may be the interference with cellular recognition of the matrix.…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…[1][2][3][4] We have previously demonstrated that fetal obstruction in the human and primate kidney causes substantial medullary injury, including interstitial expansion, peritubular a smooth muscle actin (aSMA) collar formation, and collecting duct epithelial dysfunction. 1-3 Additional work is required to further identify how medullary and collecting duct injury contributes to and modulates the pathophysiology and progression of injury following obstruction.The rodent unilateral ureteric obstruction (UUO) models are the best-described models of urinary tract obstruction [5][6][7][8][9][10][11][12][13][14][15][16] and are widely used due to their ease of manipulation and the availability of transgenic animals. These models are predominantly postnatal models with much of the work focused on the role of the proximal convoluted tubule and on late time points in which the interstitial and fibrotic responses predominate.…”
mentioning
confidence: 99%
“…The rodent unilateral ureteric obstruction (UUO) models are the best-described models of urinary tract obstruction [5][6][7][8][9][10][11][12][13][14][15][16] and are widely used due to their ease of manipulation and the availability of transgenic animals. These models are predominantly postnatal models with much of the work focused on the role of the proximal convoluted tubule and on late time points in which the interstitial and fibrotic responses predominate.…”
mentioning
confidence: 99%